Preparation of 9/65/35 PLZT thin films deposited by a dip-coating process - Simoes, A. Z.; Zaghete, M. A.; Cilense, M.; Varela, José Arana [UNESP]; Stojanovic, B. D. (Elsevier B.V., 2001)
Crack-free polycrystalline PLZT (Pb,a)(Zr,Ti)O-3 thin films with the perovskite structure were prepared by dir-coating using the Pechinis process. Lead acetate, hydrated lanthanum carbonate, zirconium n-propoxide and titanium isopropoxide were used as raw materials. The viscosity of the solution was adjusted in the range of 20 to 56 cP and the films were deposited by a dip-coating process on silicon (100) as substrate. Solutions with ionic concentration of 0.1 and 0.2 M were used. Thin film deposition was accomplished by dipping the substrates in the solution with control of withdrawal speed from 5 to 20 mm/min. The thin films were thermally treated in two steps: at 300 degreesC amid 650 degreesC. The influence of withdrawal speed. viscosity, heating rate and ionic concentration on the morphology of PLZT thin film was discussed. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: dip-coating; films; PLZT; precursors-organic; substrates; surfaces